2012
DOI: 10.1177/1352458512470862
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as a risk factor for multiple sclerosis

Abstract: This is an accepted version of a paper published in Multiple Sclerosis. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Salzer, J., Hallmans, G., Nyström, M., Stenlund, H., Wadell, G. et al. (2012) Objective: To investigate the effects of laboratory defined tobacco use on the risk for multiple sclerosis using prospectively collected biobank blood samples.Methods: Levels of cotinine were measured in n=192 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 25 publications
2
42
0
2
Order By: Relevance
“…It has a direct effect on diseases like ischemic heart disease and lung cancer and also involved in the pathogenesis of diseases like rheumatoid arthritis, diabetes mellitus and inflammatory bowel disease and immune function. [12][13][14] Studies demonstrated change in ADA activities in pleural fluid of patients with COPD which are more commonly associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…It has a direct effect on diseases like ischemic heart disease and lung cancer and also involved in the pathogenesis of diseases like rheumatoid arthritis, diabetes mellitus and inflammatory bowel disease and immune function. [12][13][14] Studies demonstrated change in ADA activities in pleural fluid of patients with COPD which are more commonly associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Øknin-gen i sykdomsrisiko er også bekreftet ved at forhøyede nivåer av kotinin (en surrogatmarkør for nikotin) ble målt i blodprøver tatt før utvikling av multippel sklerose (27). Nikotin per se er imidlertid neppe en viktig patogen faktor, da bruk av snus ikke ser ut til å øke risikoen (28) og fordi nikotin beskytter mot utvikling av multippel sklerose-liknende sykdom hos mus (29).…”
Section: Røykingunclassified
“…Sårbarhetspe-rioden for røyking er ikke avklart. I en studie var det ingen alderspåvirkning (26), mens en (27).…”
Section: Røykingunclassified
“…We have recently reported the findings of a nested case-control study where levels of cotinine, a recognized biomarker for tobacco use, were measured in biobank blood samples collected median 9 years prior to disease onset [Salzer et al 2012a]. Elevated levels of cotinine suggestive of smoking (≥10 ng/ml) [Vineis et al 2005] were associated with a 50% increased risk of MS when analyzing the entire cohort.…”
mentioning
confidence: 99%